Susceptible genetic polymorphisms and their association with adverse effects of orlistat therapy. (August 2021) - Rajan, Logesh; Radhakrishnan, Arun; Selleppan, Gobi; Mohankumar, Suresh Kumar
Abstract: Orlistat is a tetrahydrolipstatin, which inhibits both pancreatic and gastric lipase enzymes in the gut and prevents the absorption of dietary fats in the intestine. Therefore, it is widely used as an anti-obesity medication to control and manage body weight in obese patients worldwide. Despite this, the mounting number of clinical studies report that orlistat treatment induces adverse effects like pancreatitis, hepatic failure, kidney stone, acute oxalate nephropathy, and others. Although various factors could mediate the adverse effects of orlistat, emerging shreds of evidence suggest that genetic polymorphism-associated factors could be the primary reason for the cause. Hence, in this review, we first collated the most critical clinical adverse effects caused by orlistat and then appraised the susceptible genetic polymorphism that could further worsen the adverse effects of orlistat. Nonetheless, this review warrants similar conceptual approaches to understand orlistat's adverse effects in the selective genetic polymorphism and improve the therapeutic outcome of orlistat. Highlights: Orlistat is an anti-obesity medication widely used in the control and management of weight in obese patients worldwide. The orlistat acts by inhibiting the lipase enzymes and prevent the breakdown of TG in the intestine. Orlistat therapy has been cautioned with clinical adverse effects. The possible association of genetic polymorphism and adverse effects of orlistat remains elusive. Our analysis collated the selective clinically reported genes susceptible to the critical adverse effects of orlistat.